2011
DOI: 10.1002/prot.22990
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the isoelectric point of mammalian proteins as a consequence of indels and adaptive evolution

Abstract: Although important shifts in the isoelectric point of prokaryotic proteins, mainly due to adaptation to environmental pH, have been widely reported, such studies have not covered mammalian proteins, where pH changes may relate to changes in subcellular or tissue compartmentalization. We explored the isoelectric point of the proteome of 13 mammalian species. We detected proteins that have shifted their pI the most among 13 mammalian species, and investigated if these differences reflect adaptations of the ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Both sequence length and selection have been recently shown to explain the observed differences in pI between mammalian orthologs [5]. We argue that the differences in the digestive systems due to pH and compartmentalization of the different mammals is not the sole driver of major changes in pI , and that these selective changes might be due to functional divergence of the protein.…”
Section: Introductionmentioning
confidence: 74%
“…Both sequence length and selection have been recently shown to explain the observed differences in pI between mammalian orthologs [5]. We argue that the differences in the digestive systems due to pH and compartmentalization of the different mammals is not the sole driver of major changes in pI , and that these selective changes might be due to functional divergence of the protein.…”
Section: Introductionmentioning
confidence: 74%
“…In Eukaryotes, changes in the protein isoelectric point (iP) may directly influence the localization and reactions of proteins, and it is reasonable to assume that alterations to the global protein iP may interfere in interactions between proteins and complexes. Alendé et al [29], studying the evolution of iP over mammalian proteins, showed that insertions/deletions were the main reason for the shift in iP and suggested that shifts in iP might be related to the gain in additional activities, such as new interacting partners or preferences for orthologous or isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…SPDIR can generate near-random genetic variations and alter entire protein domains in a single generation. It is thus tempting to speculate that SPDIR may be an important mechanism in protein evolution (42) following gene amplification and duplication events (43) (Supporting Information).…”
Section: Discussionmentioning
confidence: 99%